Waste Bank as Green Business - Putri, S O; Mauludin, F (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of this research is to build a waste bank business using a mobile application. The method used in this research is descriptive method using a qualitative approach. Given the increasingly widespread problem of waste, one solution to this problem is that waste is processed through a waste bank. With an integrated special application, it can display a map of the location of waste banks spread across a number of areas, so that later it can be easier for the community. In addition, information about waste banks and waste education will be displayed in the application as an educational tool. The results of this study are using a mobile application to search for waste banks and increase public knowledge about waste.